2016
DOI: 10.1088/0964-1726/25/3/035025
|View full text |Cite
|
Sign up to set email alerts
|

Novel MRE/CFRP sandwich structures for adaptive vibration control

Abstract: The physical properties of magnetorheological elastomers (MRE) are a complex issue and can be influenced and controlled in many ways, e.g. by applying a magnetic field, by external mechanical stimuli, or by an electric potential. In general, the response of MRE materials to these stimuli is crucially dependent on the distribution of the magnetic particles inside the elastomer. Specific knowledge of the interactions between particles or particle clusters is of high relevance for understanding the macroscopic rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 97 publications
(150 reference statements)
1
21
0
Order By: Relevance
“…Magnetorheological elastomers (MREs) are hybrid materials, comprising an elastic non-magnetizable matrix, such as polydimethylsiloxane (PDMS), interspersed with magnetic fillers like iron oxide particles. First publications concerning such smart magnetorheological elastomers date back to the 1990s [1][2][3][4][5], though they still attract much attention today [6][7][8][9][10][11][12][13][14][15][16]. When applying a magnetic field, MREs undergo a reversible variation of their visco-elastic characteristics and/or undergo a reversible shape change that can be used for actuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetorheological elastomers (MREs) are hybrid materials, comprising an elastic non-magnetizable matrix, such as polydimethylsiloxane (PDMS), interspersed with magnetic fillers like iron oxide particles. First publications concerning such smart magnetorheological elastomers date back to the 1990s [1][2][3][4][5], though they still attract much attention today [6][7][8][9][10][11][12][13][14][15][16]. When applying a magnetic field, MREs undergo a reversible variation of their visco-elastic characteristics and/or undergo a reversible shape change that can be used for actuation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MREs offer much potential for applications in adaptive damping systems, sensors, valves, and other actuators. Their inclusion in artificial muscles, robots, medical instruments, and haptic applications is also common [6][7][8][9][10][11][12][13][14][15][16]. An efficient usage of MREs for applications would be strongly facilitated by a fundamental understanding of the macroscopic and internal mechanisms under applied magnetic fields: Their physical response to external magnetic fields depends on the influence of experimental parameters such as concentration and distribution of filler particles, matrix stiffness, magnetic field strength, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that amplitude of vibration of the MRE beam was stabilized and the stiffness and damping also improved under applied magnetic field condition. Kozlowska et al [20] analyzed the free vibration behavior of CFRP/MRE-based sandwich beam using an experimental study. Kolekar et al [21] experimentally studied the free and forced vibration parameters of a sandwich beam with MR fluid.…”
Section: Introductionmentioning
confidence: 99%
“…However, the beams eventually synchronize their motion, and this way of damping becomes ineffective-the same as in the case of identical beams and initial conditions [1]. en, the shear deformation of the soft middle layer becomes the predominant mechanism of energy dissipation in a sandwich beam [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%